Japan's sea lane security, 1940-2004 : a matter of life and death? - Graham, Euan (Nissan Institute/Routledge Japanese studies series., 2006)
This is the first major English-language study to explore the broad and longstanding connections between Japan's national security and the safety of its sea lanes. Tracing issues from pre-and post-1945 eras, the book explores how Japan's concerns with sea lane protection have developed across such diverse fields as military strategy, diplomacy, trade policy, energy security, and law enforcement. Drawing upon case study material and primary research including interviews with officials and security analysts, the book presents a chronological analysis of Japan's sea lane security. While.